1991
DOI: 10.1016/s0022-5347(17)38078-3
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Open Radioactive 125 Iodine Implantation to Control Localized Prostate Cancer: A Study of 41 Patients

Abstract: We studied 41 patients with localized prostate cancer who underwent bilateral pelvic lymphadenectomy with open insertion of radioactive 125iodine. Followup was a minimum of 5 years. Of the patients 13 died: 10 of recurrent prostatic adenocarcinoma (including 4 of 5 with pathological stage D1 cancer) and 3 of unrelated causes within 2 years of implantation without clinical evidence of prostate cancer. Of the 28 remaining patients 16 have known recurrence of cancer (positive bone scan and increasing prostate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These results corre spond to the results presented by other authors. Gottesman et al [6] reported that 10 out of 41 patients (24%) with clinically stage B or C tumours died of prostate can cer after a median follow-up period of 8 years, and only 6 patients (15%) could be considered to be clinically free of disease. Giles and Brady [7] reported a metastatic rate of 13% after 2 years of follow-up in 122 patients with stage A or B tumours and a metastatic-free survival of 60% after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…These results corre spond to the results presented by other authors. Gottesman et al [6] reported that 10 out of 41 patients (24%) with clinically stage B or C tumours died of prostate can cer after a median follow-up period of 8 years, and only 6 patients (15%) could be considered to be clinically free of disease. Giles and Brady [7] reported a metastatic rate of 13% after 2 years of follow-up in 122 patients with stage A or B tumours and a metastatic-free survival of 60% after 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although early experience with brachytherapy using freehand placement of radioactive seeds in open pelvic surgery yielded both unsatisfactory control of cancer and high post-treatment complication rates (15)(16)(17)(18), a percutaneous ultrasound-guided technique developed by Blasko, Ragde and colleagues in Seattle dramatically improved three-dimensional radiation dose distributions (13)(14)(15). As a result, brachytherapy was reevaluated (7), resulting in its now wide availability in the United States (19).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of prostate cancer by 125 I interstitial implants have been studied extensively [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with mixed results by one institution or another. A recent study from Hahnemann 25 reported results that were extremely poor compared to those reported in an earlier study at Yale, 20 or those in an Eastern Virginia Study; 17 differences in 5-yr survival rates being more than a factor of 2 ͑see Fig.…”
Section: Introductionmentioning
confidence: 99%